2022
DOI: 10.3389/fpls.2022.956210
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide analysis of basic helix–loop–helix genes in Dendrobium catenatum and functional characterization of DcMYC2 in jasmonate-mediated immunity to Sclerotium delphinii

Abstract: Dendrobium catenatum, belonging to the Orchidaceae, is a precious Chinese herbal medicine. Sclerotium delphinii (P1) is a broad-spectrum fungal disease, which causes widespread loss in the near-wild cultivation of D. catenatum. Thus, resistance breeding of D. catenatum has become the key to solve this problem. The basic helix–loop–helix (bHLH) gene family is closely related to plant resistance to external stresses, but the related research in D. catenatum is not deep enough yet. Phylogenetic analysis showed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…JA is a critical defense signaling molecule regulating different biological processes. Previous study revealed that MeJA could regulate the expression of bHLH family genes ( Zander et al., 2020 ; Guo et al., 2021 ; Li et al., 2022 ). Recently, tomato bHLH gene SlJIG has been demonstrated to be induced by JA, and function in terpene biosynthesis and resistance to insects and fungus ( Cao et al., 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…JA is a critical defense signaling molecule regulating different biological processes. Previous study revealed that MeJA could regulate the expression of bHLH family genes ( Zander et al., 2020 ; Guo et al., 2021 ; Li et al., 2022 ). Recently, tomato bHLH gene SlJIG has been demonstrated to be induced by JA, and function in terpene biosynthesis and resistance to insects and fungus ( Cao et al., 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Transcription factors have emerged as critical regulatory factors governing various aspects of plant growth, development, and response to abiotic stress. Several studies have focused on exploring transcription factor families in D. catenatum, including AP2/ERF, WOX, TCP, MYB, LBD, WRKY, HD-ZIP, MADS-box, and bHLH [40][41][42][43][44][45][46][47]. However, the characterization of the NAC transcription factor family in RJ remains unexplored.…”
Section: Identification and Analysis Of Nac Transcription Factor Fami...mentioning
confidence: 99%
“… Phylogenetic analysis of the species based on genome-wide association study of the basic helix-loop-helix (bHLH) family. The total number of bHLH transcription factors identified from the genome of each species are indicated [ 5 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 ]. …”
Section: Figurementioning
confidence: 99%